PENGGUNAAN ANALISIS RASIO LIKUIDITAS DAN RASIO SOLVABILITAS UNTUK MENGUKUR KINERJA KEUANGAN DI PT ASTRA INTERNATIONAL TBK - Kallyca Putri Almira Nursanti; Raihan Akbari; Ashira Aulia; Dafela Putri (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
This study aims to analyze the financial performance of PT Astra International Tbk during the period from 2022 to 2025, with a focus on evaluating liquidity ratios and solvency ratios. This study employs a quantitative descriptive method using secondary data obtained from the annual financial reports of PT Astra International Tbk, which have been published on the Indonesia Stock Exchange (IDX). Liquidity ratios include the Current Ratio, Quick Ratio, and Cash Ratio, while solvency ratios include the Debt to Assets Ratio (DAR) and Debt to Equity Ratio (DER). The results indicate that the company’s Current Ratio and Quick Ratio during the study period were above 1, indicating the company’s ability to meet short-term obligations is quite good. The Cash Ratio met industry standards in 2022 but declined in the following year. In terms of solvency, the DER ranged from 41% to 43.8%, and the DER reached 69.6% to 78%, which indicates that the company’s capital structure remains in a healthy condition and financial risk is classified as low. Overall, PT Astra International Tbk successfully maintained sound and stable financial conditions throughout the study period.